Compassionate reappraisal and rumination impact forgiveness, emotion, sleep, and prosocial accountability - Witvliet, Charlotte V. O.; Blank, Sabrina L.; Gall, Andrew J. (Frontiers in Psychology, 2022)
Sufficient sleep quality and quantity are important for biopsychosocial well-being. Correlational research has linked trait forgiveness to better sleep. Prior experimental evidence also demonstrated contrasting effects of offense rumination vs. compassionate reappraisal on forgiveness and psychophysiological responses, suggesting the value of testing effects on sleep. The present study assessed 180 participants (90 M, 90 F). First, we replicated an individual difference model of forgiveness, rumination, depressed and anxious affect, and sleep. Second, we conducted a quasi-experiment inducing offense rumination and compassionate reappraisal on two consecutive nights. Compassionate reappraisal (vs. rumination) replicated past research by prompting more empathic, forgiving, positive, and social responses, with less negative emotion including anger. New findings revealed that compassionate reappraisal (vs. rumination) was also associated with faster sleep onset, fewer sleep disturbances, and fewer sleep impairing offense intrusions. The morning after compassionate reappraisal, participants reported less rumination and intrusive impact of the offense, with more hedonic well-being and accountability to others. Compared to rumination, compassionate reappraisal was associated with more empathy and forgiveness, better sleep, well-being, and prosociality.